Revision of Godartiana Forster (Lepidoptera: Nymphalidae), with the description of a new species from northeastern Brazil. Issue 2 (1st August 2016) - Zacca, Thamara; Paluch, Marlon; Siewert, Ricardo; Freitas, André; Barbosa, Eduardo; Mielke, Olaf; Casagrande, Mirna
Abstract: A revision of Godartiana Forster, 1964 (Satyrinae: Euptychiina) is provided, including the description of a new species, G . amadoi Paluch, Zacca & Freitas sp. nov. from Bahia and Pernambuco, northeastern Brazil. Two genera, Cercyeuptychia L. Miller & Emmel, 1971 syn. nov. and Praefaunula Forster, 1964 syn. nov., are herein synonymised with Godartiana, based on morphological and molecular data from mitochondrial gene Cytochrome C Oxidase I and the nuclear genes GAPDH and RpS5. A new taxonomic arrangement is proposed for Godartiana, increasing to five the number of species known in this genus and also synonymising Euptychia liturata Butler, 1867 syn. nov. and E . vesper Butler, 1867 syn. nov. with G . armilla (Butler, 1867) comb. nov. The female genitalia of all species of Godartiana are described and illustrated, information is given on host plants and biology, and the previously unknown immature stages of G . muscosa are described and illustrated.